Setting National Minimum Wages for Nepal: A Need-Based Approach - Raut, Nirmal Kumar (Economic Journal of Nepal, 2019)
Method of setting minimum wages has been a debatable issue across the world. Various countries have adopted various methods of minimum wage determination process primarily formulas, government rate setting, union bargained rates, and rate recommended by an expert body. International Labour Organization (ILO) puts forth that the process of setting-up minimum wages should be scientific and accommodative of the needs of the workers and their families. Although minimum wages remains an utmost prority as a redistributive tool, studies shows that its fixation are mostly driven by political interest of the incumbent government and the interest of the private sector. Nepal is not an exception to this. This paper attempts to propose a need based method of setting minimum wages for Nepal. In addition to the food and non-food information, unlike previous need based approaches, this study uses housing information from the nationally representative household survey to derive the minimum wages for Nepal. The minimum monthly salary/wages at 2019/20 prices per household is estimated at NRs. 21799 and daily wages is estimated at NRs. 838.43.This study is expected to guide policy makers in setting evidence-based minimum wages for Nepal.